Peoples’ perception of the implementation of NHIS and its impacts on the NHIS utilization among workers of the federal agencies in the Oyo State, Nigeria (2019)
The study investigated the People’s perception of the implementation of NHIS and its impacts on the enrollees, among workers of the federal agencies in the Ibadan metropolis. It adopted a descriptive survey design. Two hundred and fifty enrollees across the federal agencies in the federal secretariat in Ibadan participated in the study. It examined the implementation of NHIS, utilization of NHIS, level of satisfaction with health care providers, the evaluation of the referral process from primary to secondary care services, distance of the health care facility, satisfaction with services at the secondary and tertiary health care levels. Data was analysed using frequency distribution, percentage and multiple regression analysis tested at 0.05 level of significance. Results revealed that more than two-third (81%) of the respondents reported visiting NHIS accredited healthcare facility in the past two years. The patient’s utilisation was high. However, nurses attitude, and waiting time were found to be the major causes of dissatisfaction. Quality service, enrollees satisfaction with services, location of the PHCs and management of the referral process have direct relationship and predicted increase in utilization rates. Independently, Service quality, enrollees’ satisfaction with services, location of the PHCs were predictors NHIS utilization. Therefore, concerted efforts should be directed by all stakeholders towards the areas of patient dissatisfaction through better service delivery.